2015
DOI: 10.1021/acsnano.5b02176
|View full text |Cite
|
Sign up to set email alerts
|

Soldering of Carbon Materials Using Transition Metal Rich Alloys

Abstract: Joining of carbon materials via soldering has not been possible up to now due to lack of wetting of carbons by metals at standard soldering temperatures. This issue has been a severely restricting factor for many potential electrical/electronic and mechanical applications of nanostructured and conventional carbon materials. Here we demonstrate the formation of alloys that enable soldering of these structures. By addition of several percent (2.5-5%) of transition metal such as chromium or nickel to a standard l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…[ 2 ] Such CNT wires may be used as conventional metal electrical conductors and may be easily introduced into already existing electrical circuits. Depending on the application the low resistance electrical connections between metal and CNT wire may be provided using a newly developed low temperature carbon solder, [ 12 ] a connecting paste based on silver or simple physical crimping.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] Such CNT wires may be used as conventional metal electrical conductors and may be easily introduced into already existing electrical circuits. Depending on the application the low resistance electrical connections between metal and CNT wire may be provided using a newly developed low temperature carbon solder, [ 12 ] a connecting paste based on silver or simple physical crimping.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanotubes currently represent a precious material for electronic engineering. Investigations into the application of the nanotubes in an industrial scale have been conducted since discovering them, starting with modern and innovative manufacturing technologies of cables using the nanotubes [45], which are likely to replace conventional conductors, through carbon nanotube fibers connection technologies [44,46], ending with ultrasensitive selective electro-sensors which have a chance to revolutionise the market. The outcomes of the investigations presented in this article are highly utilitarian and can be applied directly in industrial conditions.…”
Section: Discussionmentioning
confidence: 99%
“…have reported that widely explored MWCNTs can be utilized to revolutionize the transport of electric/electronic signal transmission of the solder, and as a result, may be suitable as reinforcement 17 . However, there is a major challenge for the employment of MWCNTs as a reinforcement material in a solder matrix due to high contact resistance (the Schottky barrier effect) at the interface between the MWCNT arrays and the solder constituents 18 , 19 . Hence, many studies have focused on their interfacial interactions because the difference in the work function between the MWCNT arrays and the solder constituents gives rise to an electron-transfer barrier that impedes electron tunneling, causing high contact resistance 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, many studies have focused on their interfacial interactions because the difference in the work function between the MWCNT arrays and the solder constituents gives rise to an electron-transfer barrier that impedes electron tunneling, causing high contact resistance 18 . There is another challenge which must be overcome to increase the reactivity of the MWCNT arrays to the solder constituents; due to the chemical inertness of MWCNTs along with low reactivity and poor diffusivity, their surfaces bond weakly with solder constituents necessary for promoting the interconnectability of electronic components 19 . These issues have been severely restricting factors for many potential applications of composite solders (including carbon nanotubes) requiring good electrical conductivity and adhesive properties.…”
Section: Introductionmentioning
confidence: 99%